Synthesis, antibacterial and cytotoxic evaluation of flavipucine and its derivatives. Issue 11 (1st June 2019) - Kusakabe, Yasuha; Mizutani, Shoma; Kamo, Shogo; Yoshimoto, Tatsuki; Tomoshige, Shusuke; Kawasaki, Tsuneomi; Takasawa, Ryoko; Tsubaki, Kazunori; Kuramochi, Kouji
Graphical abstract: Highlights: Biological activity of flavipucine and its derivatives was evaluated. Flavipucine displayed bactericidal activity against Bacillus subtilis . Flavipucine exhibited cytotoxic activity against several cancer cells. Flavipucine showed weak cytotoxic activity against non-neoplastic and normal cells. No differences in biological activity between enantiomers of flavipucine were observed. Abstract: The antibacterial and cytotoxic activity of seven racemic lactams and both enantiomers of flavipucine were evaluated. Of the compounds tested in this study, flavipucine and phenylflavipucine displayed bactericidal activity against Bacillus subtilis . These results indicate that the pyridione epoxide moiety is a pharmacophore for antibacterial activity against B. subtilis . Flavipucine showed cytotoxic activity against several cancer cells. The cytotoxic activity of flavipucine against human leukemia HL-60 cells is as strong as that of SN-38, the active metabolite of irinotecan. In contrast, the cytotoxic activity of flavipucine against nonneoplastic HEK293 cells and human normal MRC-5 cells is weaker than that of SN-38. No significant differences in the biological activity of the racemates or enantiomers of flavipucine were observed.